Pembaharuan Pendidikan Islam Perspektif Said Nursi dan Relevansinya dengan Era Society - Khojir, Khojir; Sudadi, Sudadi; Jaeni, Muhamad; Ramadhani, Annisa Laily; Syahrani, Nabila; Indriansyah, Hizbul Aulia (FENOMENA, 2022)
The rapid development of the times greatly influenced education, many problems occurred such as the dichotomy of science and so on, western leaders suggested that science and religious science were not related to each other, a Turkish Muslim figure, Said Nursi made efforts to overcome the dichotomy of science, namely by sparking thoughts of integration of science. This article aims to analyze Said Nursi's thoughts regarding the integration of education and the relevance of Said Nursi's thinking to Indonesian education. This research uses a qualitative approach with the type of library research. Data acquisition techniques are taken from several reference sources such as journals, e-books and other references relevant to the research theme. The data analysis of this study is a descriptive model. The result obtained from this research is that the integration of science according to Said Nursi is the union of religious science and science. Said Nursi wrote down his thoughts contained in his work, namely the Risalah an Nur, suggesting that the system of implementing education cannot negate religion, because religious science is the light of conscience while modern sciences are the light of reason, the truth will become clearly visible by combining the two sciences. The relevance of Said Nursi's thoughts regarding the integration of science with Islamic education in Indonesia can be seen from the aspects of the curriculum applied in Indonesia, one of which is the 2013 curriculum. The 2013 curriculum not only focuses on science but also focuses on religious science to shape the character of students who have faith and insight.